Rola aktywnego obywatela w procesie demokratyzowania demokracji na przykładzie Polski po 1989 roku - Goworek, Katarzyna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
Democracy is not an ideal system and probably will never be, but it still aspires to be ideal. What’s more, democracy is not only an institution, but a set of ideals, which are crucial to make this system function effectively. A citizen − active, committed and aware of his influence to a country − is one of the cores of the democracy and plays a major role in a subsequent democrati¬zing, i.e. improving the democratic system and influencing it’s quality. Electoral par¬ticipation is one of the fundamental activities of citizens in a democratic country. Although Poles declare that participation in election is an important feature of democracy, electoral turnout does not reflect this. In this article author triesto analyze reasons of low turnout and electoral absenteeism in Poland.